Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1108/ijhrh-11-2020-0102
|View full text |Cite
|
Sign up to set email alerts
|

“The door has opened”: moving forward with menstrual health programming in Bangladesh

Abstract: Purpose In Bangladesh, as elsewhere, menstruation is surrounded by stigma, silence, and shame. Despite being a critical part of women’s and girls’ sexual and reproductive health and rights (SRHR), it remains significantly under-researched and addressed. However, the focus on menstrual health (MH) programming is growing globally, with increased awareness of the importance of holistic and rights-based approaches. This case study aims to examine and reflect upon the MH landscape and programming in Bangladesh, ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…The findings of our study are consistent with the evolving nature of school attendance since both urban and rural students’ absence from school decreased from 25% to 14% throughout this time. Remarkably, these findings reflect the findings of an article, how MHM programme is contributing to reduced absenteeism over time [ 32 ]. Notably, our findings are similar to previous studies undertaken in South Africa and Ghana [ 33 , 34 ].…”
Section: Discussionsupporting
confidence: 86%
“…The findings of our study are consistent with the evolving nature of school attendance since both urban and rural students’ absence from school decreased from 25% to 14% throughout this time. Remarkably, these findings reflect the findings of an article, how MHM programme is contributing to reduced absenteeism over time [ 32 ]. Notably, our findings are similar to previous studies undertaken in South Africa and Ghana [ 33 , 34 ].…”
Section: Discussionsupporting
confidence: 86%
“…Indications within the submitted questions that girls had heard they should not take pain relief medicine for menstrual cramps is consistent with studies in other countries such as Uganda [ 43 ] and Malawi [ 44 ] that have reported concerns that taking pain medication for menstrual cramps could negatively affect a girl’s health and fertility. Menstrual pain is a significant concern of schoolgirls but has been under-addressed by menstrual health and hygiene programming [ 45 ] and under-researched in LMICs [ 46 ], where attention has been more narrowly focused on the impact of poor access to sanitation facilities and reliable menstrual materials on girls’ attendance at school [ 47 , 48 ]. Notably, questions about menstrual pain and its management were substantially more common in our study than questions about menstrual hygiene practices.…”
Section: Discussionmentioning
confidence: 99%
“…Bangladesh is a Muslim-majority country, and menstruating women are considered impure to undertake rituals within Islam [ 56 ]. Further, many of the questions requested clarifications about food restrictions which are common in Bangladesh [ 36 , 45 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…The AMEHC Study is situated in Bangladesh, a country with world-leading prioritisation of adolescent MH national strategy, and interventions delivered through national and international non-governmental organisations (NGOs). 38 Thus, findings from the AMEHC Study can be positioned to influence policy and programming nationally, while addressing global research questions about the relationships between MH exposures and outcomes. Our study brings together research institutions and NGO partners to support stakeholder engagement and rapid translation of the findings relevant to policy and practice.…”
Section: Study Settingmentioning
confidence: 99%